The Absence of ENT Clinics and Healthcare Access for Residents in Adankwame, Ghana - Agyemang, Cecilia Opoku; Opoku, Oscar Agyemang (Journal of Health Sciences and Medical Development, 2025)
The idea of bringing ENT services closer to the community remains a key component of reducing the burden of ENT conditions across low and middle-income countries such as Ghana. Yet there remains a shortage of special ENT clinics and specialists to manage these conditions. In light of this, the study aimed to assess the effects of non-existent ENT clinics on residents seeking health care at Adankwame Health Center in the Atwima Nwabiagya North District. A descriptive cross-sectional survey design was used with a quantitative approach. The population for the study was all residents above 15 years who visited Adankwame Health Center within the period of study. With the aid of the convenience sampling technique, 100 respondents were selected for the study. Data collection was done with a well-structured questionnaire after an ethical clearance had been sought from the Institutional Review Committee.  The data collected was analyzed into frequency tables, pie charts, and graphs, using data analysis software and SPSS 25.0. The study concluded that general knowledge and awareness of the ENT clinic were high among residents who attended Adankwame Health Centre. Hearing impairments, chronic ENT conditions, and delayed speech were some of the physiological effects identified. Parental depression probably due to children suffering from delayed speech and language was the psychological effect identified in this study.  The financial burden was seen in all aspects as respondents complained of the high cost of transportation in seeking ENT care from secondary and tertiary facilities outside the Adankwame community.